Alphaflexiviridae in Focus: Genomic Signatures, Conserved Elements and Viral-Driven Cellular Remodeling - Jesús R. Úbeda; Miguel A. Aranda; Livia Donaire (Viruses)
The family Alphaflexiviridae comprises plant- and fungus-infecting viruses with single-stranded, positive-sense RNA genomes ranging from 5.4 to 9 kb. Their virions are flexuous and filamentous, measuring 470–800 nm in length and 12–13 nm in diameter. The family includes 72 recognized species, classified into six genera: Allexivirus, Lolavirus, Platypuvirus, Potexvirus (plant-infecting), and Botrexvirus and Sclerodarnavirus (fungus-infecting). The genus Potexvirus is the largest, with 52 species, including Potexvirus ecspotati (potato virus X), an important crop pathogen and plant virology model. The genera are distinguished by genome organization and host range, while species differentiation relies on nucleotide and protein sequence identity thresholds. In this review, we summarize the current knowledge on the genomic structure, conserved genes, and phylogenetic relationships within Alphaflexiviridae, with a particular focus on the replicase and coat protein genes as signature markers. Additionally, we update the model of cellular remodeling driven by the triple gene block proteins, which are essential for virus movement, among other viral functions. Beyond their biological significance, alphaflexiviruses serve as valuable models for studying virus–host dynamics and hold potential applications in plant disease control and biotechnology. This review provides an updated framework for understanding Alphaflexiviridae and their broader impact on plant virology.